Swedish journalists and public relations officers 1989 - Petersson, Olof; Carlberg, Ingrid (Uppsala University, 1992)
Within the report on power ´Maktutredningen´, several studies of the creation of public opinion and its influence on the exercise of power in Sweden were carried out. The purpose of this survey is to describe some key groups within the media and information society. The questionnaire contained questions about social background, education, professional experience and work situation. The central point in the questionnaire was on the judgement of the role of mass media in society. Most of the questions were common to both journalists and public relation officers.

Within the report on power ´Maktutredningen´, several studies of the creation of public opinion and its influence on the exercise of power in Sweden were carried out. The purpose of this survey is to describe some key groups within the media and information society. The questionnaire contained questions about social background, education, professional experience and work situation. The central point in the questionnaire was on the judgement of the role of mass media in society. Most of the questions were common to both journalists and public relation officers.
Svenska journalister och informatörer 1989
Keywords: Media; Media; Working conditions; Arbetsförhållanden; Social Sciences; Samhällsvetenskap